Case Report: Identification of Novel Variants in ERCC4 and DDB2 Genes in Two Tunisian Patients With Atypical Xeroderma Pigmentosum Phenotype - Nabouli, Imen; Chikhaoui, Asma; Othman, Houcemeddine; Elouej, Sahar; Jones, Meriem; Lagarde, Arnaud; Rekaya, Meriem Ben; Messaoud, Olfa; Zghal, Mohamed; Delague, Valerie; Levy, Nicolas; De Sandre-Giovannoli, Annachiara; et al. (Frontiers in Genetics, 2021)
Xeroderma Pigmentosum (XP) is a rare genetic disorder affecting the nucleotide excision repair system (NER). It is characterized by an extreme sensitivity to sunlight that induces cutaneous disorders such as severe sunburn, freckling and cancers. In Tunisia, six complementation groups have been already identified. However, the genetic etiology remains unknown for several patients. In this study, we investigated clinical characteristics and genetic defects in two families with atypical phenotypes originating from the central region in Tunisia. Clinical investigation revealed mild cutaneous features in two patients who develop multiple skin cancers at later ages, with no neurological disorders. Targeted gene sequencing revealed that they carried novel variants. A homozygous variation in the ERCC4 gene c.1762G>T, p.V588F, detected in patient XP21. As for patient XP134, he carried two homozygous mutations in the DDB2 gene c.613T>C, p.C205R and c.618C>A, p.S206R. Structural modeling of the protein predicted the identified ERCC4 variant to mildly affect protein stability without affecting its functional domains. As for the case of DDB2 double mutant, the second variation seems to cause a mild effect on the protein structure unlike the first variation which does not seem to have an effect on it. This study contributes to further characterize the mutation spectrum of XP in Tunisian families. Targeted gene sequencing accelerated the identification of rare unexpected genetic defects for diagnostic testing and genetic counseling.